Erythraeid mites (Prostigmata, Erythraeidae) from Saudi Arabia, description of three new species and a new record - Muhammad Kamran; Fahad Jabr Alatawi (ZooKeys, 2014)
Three erythraeid genera Balaustium von Heyden, Charletonia Oudemans, and Erythraeus Latreille (Trombidiformes: Prostigmata) are reported for first time from Saudi Arabia based on three new larval species, B. yousifi sp. n., C. bahaensis sp. n., and E. (Erythraeus) uhadi sp. n. and one new record Erythraeus (Zaracarus) lancifer Southcott. All the three new species are described and illustrated from larvae.